Semen collection and artificial insemination in cockatiels (Nymphicus hollandicus) – A potential model for psittacines - Neumann, D.; Kaleta, E. F.; Lierz, M. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2013)
Study: Since many psittacine species are endangered and also rare in captivity, the number of offspring produced from breeding is crucial. Many potential breeding birds in species conservation programs are force-paired, and the eggs of many clutches are frequently infertile. Furthermore, male infertility is a common problem. The use of artificial insemination may increase the number of fertile eggs. Material and methods: In this study, 32 cockatiels (Nymphicus hollandicus) were divided into two groups. In one group, the males were endoscopically sterilised. The males of the other group were used as semen donors. After collection using a novel massage technique, semen samples were examined microscopically to assess contamination and quality. Samples with medium to high sperm concentrations, medium to high motility and no contaminants were used for intracloacal artificial insemination of hens in the group with sterile males. Results: In total, 74.2% of all attempts to collect semen were successful. Insemination resulted in fertilisation of 17 of 23 eggs (73.9%), which was slightly lower than the natural fertilisation rate (88.4%). No negative effects were observed on the oviposition interval of the inseminated hens throughout the entire study. Clinical relevance: Easily applicable in veterinary practice, this study demonstrates that the use of artificial insemination may be a valuable tool to address reproductive failure of psittacines in breeding projects.
Keywords: Parrots; budgerigar; semen collection; semen analysis; species conservation